Risk of Human Papillomavirus (HPV) Infection and Cervical Neoplasia after Pregnancy. Issue 1 (December 2015) - Trottier, Helen; Mayrand, Marie-Hélène; Baggio, Maria; Galan, Lenice; Ferenczy, Alex; Villa, Luisa; Franco, Eduardo
Abstract Background Parity is well established as a risk factor for cervical cancer. It is not clear, however, how pregnancy influences the natural history of HPV infection and cervical neoplasia. Our objective was to study the risk of HPV infection and cervical squamous intraepithelial lesions (SIL) after pregnancy. Methods We used the Ludwig-McGill cohort study which includes 2462 women recruited in Sao Paulo, Brazil in 1993–97 and followed for up to 10 years. Cellular specimens were collected every 4–6 months for Pap cytology and HPV detection and genotyping by a polymerase chain reaction protocol. Study nurses recorded pregnancy occurrence during follow-up. HPV and Pap results from pregnant women were available before and after, but not during pregnancy. The associations between pregnancy and post-partum HPV infection/SIL were studied using generalized estimating equation models with logistic link. Adjusted odds ratios (OR) were estimated with empirical adjustment for confounding. Results We recorded 122 women with a history of pregnancy during follow-up. Of these, 29 reintegrated the cohort study after delivery. No association between HPV and pregnancy was found. A single SIL case (high grade SIL) occurred post-partum. Likewise, there was no association between pregnancy and risk of low grade SIL or any-grade SIL at the next visit (adjusted OR = 0.84, 95 % CI: 0.46-15.33) after controlling for confounders. Conclusions No associations were found between pregnancy and HPV or LSIL. The single observed case of HSIL post-partum was more than would be expected based on the rate of these abnormalities among non-pregnant women. As this association was found with only one case, caution is required in the interpretation of these results.